2021
DOI: 10.1016/j.ecns.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Simulations with Standardized Patients for Nursing Students in Preparation for Clinical Placements in Mental Health Care

Abstract: Background: Nursing students often express uncertainty about clinical placement in a mental health care setting. Simulation with standardized patients may provide an opportunity for students to explore clinical situations in mental health nursing before their clinical placement, thereby increasing these students' overall satisfaction and confidence levels with regard to mental health nursing. Method: A qualitative descriptive design was selected. Twenty-four undergraduate nursing students participated in four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…This finding indicates that participating students were highly satisfied with the use of simulated patients in learning psychiatric nursing clinical competencies. These results are congruent with recent studies by Amsalem et al, Ma et al, Ozkara San et al, and Presno et al [ 21 , 22 , 23 , 24 ], indicating that standardized patient simulation can effectively improve undergraduate nursing students’ learning satisfaction in mental health nursing and help to prepare them for their real clinical placements. In addition, Johnson et al and Goh et al [ 25 , 26 ] found that using simulated patients in undergraduate mental health nursing education significantly increased students’ satisfaction before being posted to mental health settings for their clinical attachment.…”
Section: Discussionsupporting
confidence: 91%
“…This finding indicates that participating students were highly satisfied with the use of simulated patients in learning psychiatric nursing clinical competencies. These results are congruent with recent studies by Amsalem et al, Ma et al, Ozkara San et al, and Presno et al [ 21 , 22 , 23 , 24 ], indicating that standardized patient simulation can effectively improve undergraduate nursing students’ learning satisfaction in mental health nursing and help to prepare them for their real clinical placements. In addition, Johnson et al and Goh et al [ 25 , 26 ] found that using simulated patients in undergraduate mental health nursing education significantly increased students’ satisfaction before being posted to mental health settings for their clinical attachment.…”
Section: Discussionsupporting
confidence: 91%
“…This study was conducted to determine variations in outcomes when comparing mental health simulation utilizing mannequins versus standardized patients. The findings from this study are consistent with prior evidence that supports the benefits of both simulation modalities, including increased confidence, satisfaction, knowledge, and communication skills (Brown, 2015; Foley & Robinson, 2021; Hall, 2017; Knutson de Presno et al, 2021; Pfeiffer & Wands, 2021). The findings from this study also expand the literature by comparing differences in knowledge, satisfaction, debriefing, clinical reasoning, clinical learning, and overall evaluation when using mannequins versus standardized patients in mental health nursing simulation.…”
Section: Discussionsupporting
confidence: 88%
“…Results from an integrative literature review revealed enhanced confidence, self-awareness, and clinical skills, as well as a decrease in anxiety when utilizing standardized patients in mental health simulation (Øgård-Repål et al, 2018). Researchers have noted that there is an increase in confidence and communication skills when nursing students engage in mental health simulation and that nursing students unanimously prefer standardized patients as the modality for mental health simulation (Foley & Robinson, 2021; Knutson de Presno et al, 2021; Pfeiffer & Wands, 2021). Another key factor in the success of standardized patients is the realism impact that has been expressed by students (Doolen et al, 2014; Jack et al, 2014; Meerdink & Khan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of mental health, a systematic review by Brown in 2015 found that simulation augmented student skills in therapeutic communication and assessment for this specialty. Both quantitative and qualitative research disseminated during the pandemic has continued to support the role of simulation as a valuable component of the psychiatric nursing clinical experience (Arnone et al, 2021; de Presno et al, 2021; García-Mayor et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This requires providing a supportive environment that promotes student nurse well-being and the capacity to adapt (Cha et al, 2020; Wenzel et al, 2022). Furthermore, foundational knowledge provided by mental health nursing clinical simulations can support the education of student nurses to serve as safe and competent professional nurses in the mental health setting (Arnone et al, 2021; de Presno et al, 2021; García-Mayor et al, 2021). Implementing practices that provide safe, high-quality clinical learning environments for student nurses is essential to improve mental health outcomes in the wake of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%